Revealing Hidden UV Instabilities in Organic Solar Cells by Correlating Device and Material Stability. Issue 39 (3rd September 2019) - Classen, Andrej; Heumueller, Thomas; Wabra, Isabell; Gerner, Johannes; He, Yakun; Einsiedler, Lukas; Li, Ning; Matt, Gebhard J.; Osvet, Andres; Du, Xiaoyan; Hirsch, Andreas; Brabec, Christoph J.
Abstract: With state‐of‐the‐art organic solar cells (OSCs) surpassing 16% efficiency, stability becomes critical for commercialization. In this work, the power of using photoluminescence (PL) measurements on plain films is demonstrated, as well as high‐performance liquid chromatography analysis to reveal the origin of UV instabilities in OSCs based on the most commonly used acceptors PC70 BM ([6, 6]‐phenyl‐C71‐butyric acid methyl ester), ITIC (3, 9‐bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone))‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐d:2′, 3′‐d′]‐s‐indaceno[1, 2‐b:5, 6‐b′]dithiophene), and o‐IDTBR (indacenodithiophene‐based non‐fullerene acceptor). The UV dependent stability tests reveal instabilities in solar cells based on PC70 BM and ITIC while devices based on o‐IDTBR are highly stable even under UV illumination. The analysis of solar cell devices based on charge extraction and sub‐bandgap external quantum efficiency only shows the UV‐dependent emergence of traps, while PL spectra of plain films on glass allows the disentanglement and identification of individual instabilities in multi‐component bulk‐heterojunction devices. In particular, the PL analysis demonstrates UV instabilities of PC70 BM and ITIC toward the processing additive 1, 8 diiodooctane (DIO). The chemical analysis reveals the in‐depth mechanism, by providing direct proof of photochemical reactions of PC70 BM and ITIC with UV‐induced radicals of DIO. Based on this scientific understanding, it is shown how to stabilize PBQ‐QF:PC70 BM devices. Abstract : The UV stability of organic solar cells is investigated and by using photoluminescence and high‐performance liquid chromatography it is shown that UV instabilities observed in devices originate from UV instabilities from individual components in multi‐component bulk heterojunction active layers. In particular, the UV instabilities of commonly used acceptors toward the highly used processing additive 1, 8‐diiodooctane are revealed.